Meticulous parade on naringin respecting its pharmacological activities and novel formulations - Mahboob Alam; Farogh Ahsan; Tarique Mahmood; Arshiya Shamim; Saba Parveen; Mohammad Shariq; Vaseem Ansari (Mashhad University of Medical Sciences, 2022)
Objective: Medicinal plants having antioxidant potential possess numerous constituents which are responsible for different beneficial effects and are used as an alternative resource of medicine to lessen diseases linked with oxidative stress. Flavonoids are identified in the plants since ages and display wide spectrum of biological actions that might be able to stimulate the steps which are disturbed in different diseases. Flavonoids are significant natural compounds with various biologic properties, among which the most common is the anti-oxidant potential.Citrus flavonoids establish an important stream of flavonoids. Naringin, very common flavonoids present in the diet, belongs to the family of flavanone. It is the principal constituent of citrus family that contains flavonoids for example tomatoes, grapefruits and oranges.Materials and Methods: In this article, we reviewed naringin with respect to sources, chemical property, pharmacokinetics, pharmacological activity, and novel formulations. The literature survey has been done by searching different databases such as Psyc INFO, Science Direct, PubMed, EMBASE, Google, Google Scholar, Medline.Results: Naringin is known to behave as an antioxidant and possess anti-inflammatory, anti-apoptotic, anti-atherosclerotic, neuroprotective, anti-psychotic, anti-asthmatic, anti-diabetic, hepatoprotective, anti-tussive, cardioprotective, and anti-obesity activity. Further clinical studies using large sample sizes remain essential to obtain the appropriate dose and form of naringin for averting diseases. Furthermore, the therapeutic approach of these bioflavonoids is significantly inappropriate due to the lack of clinical evidence. Different plants must be explored further to find these bioflavonoids in them.Conclusion: The results of this exploration provides biological actions of bioflavonoid (naringin), predominantly on pharmacological and novel dosage forms of naringin.